Fluoxetine minimally affects hearing loss but induces gene expression changes in the cochlear nuclei after noise exposure - Hyun-Ju An; Sujin Choi; Soonchul Lee; Hyunjeong Yeo; So Young Kim (PLoS ONE, 2026)
Purpose This study investigated the effects of fluoxetine on noise-induced injuries to the cochlea and auditory nerve, with a focus on its impact on perineuronal nets (PNNs) and gene expression changes in the ventral cochlear nuclei (VCN). Methods Sprague-Dawley rats were exposed to white noise at 115 dB SPL for 3 hours per day over 3 weeks. After measuring auditory brainstem response (ABR) thresholds, rats were treated with fluoxetine (10 mg/kg) for 19 days. Four groups were included (vehicle, fluoxetine, noise + vehicle, and noise + fluoxetine; n = 10 per group). ABR measurements, analysis of extracellular baskets in cochlear ribbon synapses and PNNs, and RNA sequencing of the VCN were performed. Results Following fluoxetine treatment, noise-exposed rats (noise + fluoxetine group) showed hearing thresholds comparable to those in the noise + vehicle group. Both noise-exposed groups exhibited cochlear hair cell loss and disorganization. Extracellular baskets surrounding cochlear ribbon synapses were significantly reduced in noise + vehicle rats and were not restored in noise + fluoxetine rats. Aggrecan expression in the VCN was reduced in the noise + fluoxetine group. RNA sequencing revealed upregulation of genes including Mal, Fos, Rapgef3, Papss2, Adamts4, and Heph, and downregulation of genes such as Pde5a, Kcnma1, Nr4a1, Dlgap3, Slc18a2, and Dgkg . Conclusion Fluoxetine exerted only modest, 4 kHz‑restricted improvements in ABR thresholds and did not restore cochlear structure or normal hearing following noise‑induced hearing loss. However, it induced distinct transcriptional alterations in the VCN and modulated the extracellular environment, suggesting a potential role in neural remodeling rather than direct auditory restoration.